Changing Attitudes toward Location-Based Advertising in the USA and Finland. Issue 1 (2nd January 2018) - Kini, Ranjan B.; Suomi, Reima
ABSTRACT: Ever since smartphones and tablets have become pervasive and GPS technologies have become more accurate and sophisticated, there is a changing attitude toward the acceptance of location-based advertising (LBA) by the new generation of users. In this research, college students from the United States and Finland are exposed to scenario-based situation of LBA to measure perceived values of LBA and their privacy perceptions. The results from the study show that there are those who find LBA valuable and those who find it infringes on their privacy. Authors also found differences in the responses to situations where permission is given and the advertisements are relevant and the context is important.